Safety training – crucial in anaesthesiology education - Fenrych, Urszula; Lipska, Julia; Hamerska, Laura; Hamerska, Julia; Bocianiak, Bogumił; Antczak, Joanna; Kajka, Anna; Wojtczak, Karolina; Skupińska, Olga; Ruta, Damian (Quality in Sport, 2024)
Anaesthesiologists are responsible for procedures performed in a multidisciplinary team. The complexity of procedures, the burden of responsibility, time pressure, efficiency demands, psychological and physiological limitations, the necessity for quick and accurate decision-making, and many other challenges pose a risk of error. The purpose of this paper is to highlight the role of human factors in the occurrence of errors during anaesthesia procedures, as well as to identify strategies, which implementation into the training process and clinical practice of anaesthesia could support the safety of the therapeutic process. This paper discusses selected issues that, in our opinion, should be a permanent element of training and periodic qualification improvement among anesthesia team members.